The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1246/cl.1983.1863
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Spectra of Heat-Treated Poly(vinyl Alcohol) Film

Abstract: Among species of general structure (\( \llap–CH=CH \llap–)\)n produced in the heat-treated PVA substrate, the existence of polyene systems with n=2 to 5 were successfully confirmed by means of the excitation spectra and the Lewis–Calvin’s plot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The formation of the conjugated polyene structures in the thermal degradation of PVC and PVA is mainly via dehydrochlorination [21][22][23][24][25][26][27][28][29][30][31][32] and dehydration [33][34][35] , respectively. The effects of the preirradiation on the conjugated structure formation observed in this work are believed to be related to the radiation-induced structure changes on the polymer chains as well as the generated small molecular products.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the conjugated polyene structures in the thermal degradation of PVC and PVA is mainly via dehydrochlorination [21][22][23][24][25][26][27][28][29][30][31][32] and dehydration [33][34][35] , respectively. The effects of the preirradiation on the conjugated structure formation observed in this work are believed to be related to the radiation-induced structure changes on the polymer chains as well as the generated small molecular products.…”
Section: Discussionmentioning
confidence: 99%
“…While the ultraviolet absorption provides only very indistinct evidence of the chromophores which cause the yellow discoloration-the only prominent mid-ultraviolet peak at 280nm may derive not from the discolored polymer but from a non-ionic surfactant containing a benzene ring-the increase of absorption across a broad wavelength region and the evidence of a series of absorption peaks occurring at regular intervals suggest a similarity to the chromophores which are produced in vinyl polymers such as polyvinyl alcohol (PVOH) [17,18] and polyvinyl chloride (PVC) [19]. In these other polymers, discoloration arises from 'polyene' structures, carbon chains containing conjugated double bonds (alternating single and double carboncarbon bonds in sequence along the chain).…”
Section: Discussionmentioning
confidence: 99%
“…Strong fluorescence of these polyene chromophores has been noted in studies of PVOH [17,18] and, because of the importance of these polyene structures in biological vision systems, the absorption and fluorescence properties of these compounds have been studied in great detail. It has been found that the fluorescence can only occur in moderate-length chromophores with four to eight double bonds (including the terminal carbonyl) having an unusual ordering of lowlying excited states [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This dependence often derives from restrictions on the transport of reagents to within short distances from a surface or interface in a material. A classic effect is the yellowing of many polymers [2][3][4][5][6][7][8][9][10][11][12][13] under exposure to UV radiation. This process occurs efficiently in zones of a material in which oxygen concentrations are low or negligible, at depths of tens or hundreds of micrometers below the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In poly(vinyl chloride) (PVC) [2][3][4][5][6][7][8][9] and related polymers such as poly(vinyl alcohol) (PVA) [10][11][12] and poly(vinyl acetate) (PVAc), 13 when thin films are subjected to thermal or UV photo-degradation, yellowing arises from the for-mation of poly(ene) chains of structure -(CHϭCH) n -. As degradation proceeds, the chain length n increases from 2-4 through 12 units or greater, 7,12 producing increased visible wavelength absorption in sub-surface zones.…”
Section: Introductionmentioning
confidence: 99%